2012
DOI: 10.1118/1.4737096
|View full text |Cite
|
Sign up to set email alerts
|

A dose point kernel database using GATE Monte Carlo simulation toolkit for nuclear medicine applications: Comparison with other Monte Carlo codes

Abstract: In this study, the authors have checked GATE's reliability for absorbed dose calculation when transporting different kind of particles, which indicates its robustness for dosimetry applications. A novel dataset of DPKs is provided, which can be applied in patient-specific dosimetry using analytical point kernel convolution algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 31 publications
3
80
0
1
Order By: Relevance
“…Several studies have assessed the applicability of the GATE Monte Carlo package for internal dosimetry of radionuclides and related applications [3,4,20,21]. A brief summary of these studies can be found in a published review by Sarrut et al [22].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have assessed the applicability of the GATE Monte Carlo package for internal dosimetry of radionuclides and related applications [3,4,20,21]. A brief summary of these studies can be found in a published review by Sarrut et al [22].…”
Section: Introductionmentioning
confidence: 98%
“…Now we aim to estimate the dose with respect to the materials used for proton irradiation. So, these are analyzed by Bragg-Gray cavity theory [16] which deals with stopping power of particles is energy absorbed per unit mass is weighted ratio of mass stopping power.…”
Section: Iii1 Dose Estimationmentioning
confidence: 99%
“…Indeed, ADs may be estimated by means of several methods, such as the MIRD approach using S-values for doses at organ-level [7, 8], dose point kernel (DPK)-based convolution [911], or Monte Carlo (MC) for doses at pixel-level. MC is considered the reference method, and several comparisons with the others methods were performed and analyzed [10, 1214]. …”
Section: Introductionmentioning
confidence: 99%